Initiating a Modern Pesantren with Agribusiness Skills as an Effort to Prosper the Community Ciherang Village, Kec. Ciomas, Kab. Bogor, West Java - Saihul; Pakkanna, Mukhaer (PT FORMOSA CENDEKIA GLOBAL, 2024)
Islamic boarding schools are traditional Islamic educational institutions that exist only in Indonesia, have become an integral part of the culture of Islamic education in Indonesia and are synonymous with studying the yellow book away from the hustle and bustle of the business world. The purpose of this research is to determine the education process, design an education model in a modern Indonesian Agro Boarding School with agribusiness skills. This research also conducted a SWOT analysis to determine management strategies, as well as the internalization process. The object of research is a modern boarding school in West Java. The research method used qualitative analysis using SWOT analysis. Collective data is done by distributing questionnaires and indept interviews. Informants used as data sources are boarding school administrators. The results prove that the educational process in pesantren is grouped into two parts of learning religious knowledge and enterpreunership skills. The enterprenership education model is designed according to the talents of the students in the field of agribusiness with each accompanied by a tutor. Based on the results of the Swot analysis, the management strategy that can be applied is a growth strategy and strengthens the internalization of management. The implications of the research change the paradigm of the pesantern cottage as a place to create Islamic entrepreneurship and competitiveness